IMPROVING THE DISCIPLINE OF EARLY CHILDHOOD EDUCATION CHILDREN WITH THE PRACTICE OF PARKING BACKWARDS (KINDERGARTEN WIDYAKUSUMA SALADARA ISLAMIC KINDERGARTEN, CIREBON CITY) - Retno Widyani; Mus Nilamcaya; Mohammad Yusup; Djohan Rochanda Wiradinata; Ratna Dumilah; Gratia Leti permana (Jurnal Abdisci, 2026)
Based on the initial observations that the researchers have made at Kindergarden Islam Widyakusuma Saladara in Cirebon city identified several problems such as: Flag ceremony activities there are 3 children at the time of marching still playing / children have not been disciplined in marching the cause is There are 2 teachers who are allowed to attend suddenly so that there are fewer accompanying personnel, children scramble to run out of class to the mosque to carry out dhuha prayers and there are 3 children who fall because they are pushed (blm children can have an orderly culture and queue) the cause is the teacher focuses on tidying up the class and waiting for students who have not left the class and letting the other children go out first, at the time of the dhuha prayer in the mosque most of the children have not been able to keep their slippers neatly in their place, the cause is that children are in a hurry and want to enter the mosque immediately, do not want to be orderly and queue. Thus, the researcher concluded that the root of the problem lies in the level of discipline and order, both in teachers and children. From several problems identified, the researchers chose the problem during dhuha prayers in mosques: children have not been able to store their sandals neatly in their place. This is because order and discipline require a process and time to get used to. So, it is necessary to start with small things, namely storing your sandals neatly.